2010
DOI: 10.1051/0004-6361/200913575
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the broad iron Kαline in neutron-star LMXBs withXMM-Newton

Abstract: We analysed the XMM-Newton archival observations of 16 neutron star (NS), low-mass X-ray binaries (LMXBs) to study the Fe K emission in these objects. The sample includes all the observations of NS LMXBs performed in EPIC pn timing mode with XMM-Newton publicly available until September 30, 2009. We performed a detailed data analysis considering pile-up and background effects. The properties of the Fe lines differed from previous published analyses because of either incorrect pile-up corrections or different c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
163
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(175 citation statements)
references
References 59 publications
10
163
2
Order By: Relevance
“…Nonetheless, both the results of Pandel et al (2008) and Cackett et al (2010) are based on data which were not corrected for pileup effects. As demonstrated by Ng et al (2010), re-analyses of the same XMM-Newton data considering pileup and background effects, suggested a different iron line profile. Ng et al (2010) found that the Fe lines in the three spectra of 4U 1636-53 used by Pandel et al (2008) appeared to be symmetric and could be well fit with a Gaussian profile, although, due to the statistics, a relativistic origin of the line could not be excluded.…”
Section: U 1636-53mentioning
confidence: 89%
See 4 more Smart Citations
“…Nonetheless, both the results of Pandel et al (2008) and Cackett et al (2010) are based on data which were not corrected for pileup effects. As demonstrated by Ng et al (2010), re-analyses of the same XMM-Newton data considering pileup and background effects, suggested a different iron line profile. Ng et al (2010) found that the Fe lines in the three spectra of 4U 1636-53 used by Pandel et al (2008) appeared to be symmetric and could be well fit with a Gaussian profile, although, due to the statistics, a relativistic origin of the line could not be excluded.…”
Section: U 1636-53mentioning
confidence: 89%
“…As demonstrated by Ng et al (2010), re-analyses of the same XMM-Newton data considering pileup and background effects, suggested a different iron line profile. Ng et al (2010) found that the Fe lines in the three spectra of 4U 1636-53 used by Pandel et al (2008) appeared to be symmetric and could be well fit with a Gaussian profile, although, due to the statistics, a relativistic origin of the line could not be excluded. However, Ng et al (2010) did not include the simultaneous RXTE data in their fits, which can affect the Fe emission line profile that strongly depends on the underlying continuum.…”
Section: U 1636-53mentioning
confidence: 89%
See 3 more Smart Citations